A Conceptual Characterization of Value Creation in Hospitality and Tourism Firms from a Complexity Perspective. (May 2021) - Navarro-Meneses, Francisco J
Hospitality and tourism firms are suffering more than others the devastating effects of the COVID-19 pandemic. Its recovery will require designing and implementing innovative value creation strategies that are hard to imagine with the simplifying cause-and-effect analytical frameworks so widespread today. Building on the narrative of the firm as a open complex adaptive system and the literature reviewed in economics and management, this article approaches value creation from the paradigm of complexity science and provides a conceptual bases that would allow value practitioners incorporate more realistic and holistic elements to its analysis. Several implications are outlined that could result from the adoption of this perspective and that might encourage a change in the mindset of scholars and firms' managers. Guidelines for deeper exploration of value creation from complexity are also provided that could open new avenues for theoretical and methodological advance.